Đề xuất tiến trình tổ chức hoạt động nghiên cứu khoa học, kĩ thuật nhằm phát triển năng lực giải quyết vấn đề và sáng tạo cho học sinh trung học phổ thông - Do, Dung; Đặng Thị Thu Hiền, Đặng Thị Thu Hiền (Tạp chí Giáo dục, 2026)
In the context of implementing the 2018 General Education Program and promoting STEM education, scientific and technical research activities are increasingly seen as an important form of education to develop competencies for high school students. However, current research mainly focuses on the role or organizational models of scientific and technical research activities, while research proposing a process for organizing these activities based on the characteristics of scientific research and oriented towards developing problem-solving and creative abilities is limited. This study aims to propose a process for organizing scientific and technical research activities to cultivate problem-solving and creative abilities in high school students. The study uses methods of document analysis and synthesis and theoretical development to analyze the characteristics of scientific and technical research activities, manifestations of problem-solving and creative abilities, the requirements of the 2018 General Education Program, and the principles for designing the process of organizing these activities. Based on this, the study proposes a nine-step process for organizing scientific and technical research activities and illustrates its application through the topic "Introduction to Electronics" (Physics 11). The research results contribute to supplementing the theoretical basis and providing reference materials for teachers in organizing scientific and technical research activities oriented towards developing competencies for high school students.